Coping in Pediatric Burn Survivors and Its Relation to Social Functioning and Self-Concept - Snider, Mira D. H.; Young, Sarah; Enlow, Paul T.; Ahrabi-Nejad, Corrine; Aballay, Ariel M.; Duncan, Christina L. (Frontiers in Psychology, 2021)
Pediatric burn survivors experience increased risk for bullying, stigmatization, body image concerns, and problematic social functioning. Although coping behaviors are associated with engagement in social supports and positive self-concept in multiple pediatric illness populations, their relation has not been examined in pediatric burns. This study examined coping in relation to social functioning and self-concept in 51 pediatric burn survivors aged 7-17 years (M = 12.54; SD = 2.65). Survivors and their caregivers completed the Child Coping Strategies Checklist (youth report); the Burn Injury Social Questionnaire (parent and youth report); and the Piers-Harris Children’s Self-Concept Scale-2 (youth report). Associations between coping, social functioning, self-concept, demographic features, and burn injury characteristics were examined via bivariate correlations. Hierarchical linear regressions examined whether coping strategies predicted social functioning and youth self-concept beyond burn injury and demographic variables. Social functioning concerns were positively correlated with TBSA (r = .63 and .40, respectively). TBSA was the only significant predictor of parent-reported social concerns (β = .65, p < .001). Greater distraction coping predicted fewer youth-reported social concerns (β = -.39, p = .01). Greater active coping (B = .67, p = .002) and lower avoidance coping (B = -.36, p = .03) predicted better youth-reported self-concept. This study advances our understanding of coping as potentially protective for psychosocial adjustment. Clinicians working with child burn survivors should incorporate active coping interventions into treatment. Further research including larger and more diverse samples is needed to understand the role of coping approaches on psychological adjustment during burn healing.